The Rainwater Harvesting (RWH) as a flash flood mitigation measure in Ken Rimba Shah Alam, Selangor - Asmawi, M. Zainora; Mustofa, Nur Syahinda; Abd Aziz, Abdul Razak; Abdul Rahim, Asiah (RMP Publications, 2020)
Malaysia is one of the countries facing frequent flash flood problems in the urban area due to city expansion and rapid development, poor drainage system and the natural system. There is a dire need for all relevant agencies to adopt new strategies to reduce the frequencies of flash floods that are plaguing the fully developed river basins, such as the Klang River Basin. Thus, the objectives of the study are to assess the Rainwater Harvesting (RWH) practice in mitigating the occurrence of the flash flood in Ken Rimba Shah Alam, Selangor. Ken Rimba development was selected as the case study as the major interest of this research to view the community in Ken Rimba residences on awareness and acceptance towards RWH implementation in the study area as well as their perception towards RWH as a flash flood mitigation measure in the study area. The study considers the perception of the community as they are living in flood-prone areas and likely very much affected during the flash flood, especially during the heavy rain in the monsoon season. The work collected the primary data through the distribution of questionnaire surveys to 194 respondents shows that nearly half of the total respondents perceived towards RWH application as a flash flood mitigation measure in the study area. However, there is not enough awareness of RWH benefits. Thus, the study suggested promoting RWH through mass media to the public to achieve long-term sustainability and resiliency that can be a flash flood mitigation measure, particularly in the residential area. All recommendations have involved many parties to promote rainwater harvesting to safeguarding the urban areas in nurturing communities that are simultaneously coping with climate change in this rapid urbanisation area.